Motivation towards Inbound Tourism: A Study of Middle East Tourist - Sari, Dhanik Puspita (E-Journal of Tourism, 2019)
This research discusses the motivation of Middle East Tourists who come and visit Pucak areas in West Java. Puncak is an area that has a cool climate with beautiful natural scenery located not far from Jakarta, the capital city of Indonesia. Middle East tourists are a potential market for Indonesian tourism. The ampunt of the expenditure is highest compared to other tourists who visiting Indonesia. And certainly for the locals it give impacts on the economy of the surrounding community. This study uses a descriptive quantitative approach, using questionnaires and literature studies in data collection and data analysis using linear regression. Data was collected from 100 inbound Middle East tourists who travel and visited Puncak Area. The Pearson correlation was used to find the relationship between push and pull factor motivation towards their visiting decision. ANOVA and T Test used to examine the indicators. The result shows that push and pull motivation influenced the visiting decision of inbound tourism, partially and simultaneously. Relaxation got the highest score in push motivation, meanwhile the environment and weather conditions dimension got the highest score on pull motivation. Keywords: Tourist Motivation, Push and Pull Motivation, Inbound Tourism, Puncak.